Using Self-employment as Proxy for Entrepreneurship: Some Empirical Caveats - Carl Magnus Bjuggren; Dan Johansson; Mikael Stenkula (Research Institute of Industrial Economics (IFN), 2010)
Research on entrepreneurship has received an increased amount of interest in recent years, with self-employment being used as the most common proxy for entrepreneurship in empirical studies. However, there are various ways of defining self-employment, making it a somewhat dubious proxy. This may flaw the analysis, especially in cross-country studies, since the documentation of data often is insufficient and difficult to access due to language barriers. We present an analysis of Swedish self-employment data. We show that the measurement of self-employment has changed over time to noticeably affect the reported number of self-employed in the two major statistical sources on self-employment. The reported development of self-employment sometimes differs diametrically depending on source. Sweden is occasionally erroneously reported to show the largest increase in self-employment in cross-country studies. Our study mimics the results of other country-specific analyses and we conclude that well-grounded conclusions require that the advantages and disadvantages of different statistical sources are recognized.
Keywords: C81; C82; L26; M13; 330; Labor Force Survey; RAMS; Self-employed; Self-employment; Entrepreneurship; Selbstständige; Messung; Unternehmer; Arbeitskräfte; Arbeitsmarktstatistik; Schweden